PENDAMPINGAN PENGEMBANGAN DESAIN DAN MANAJEMEN USAHA PRODUK KERAJINAN ANYAMAN PANDAN DI DESA ALUE DUA MUKA O KECAMATAN IDI RAYEUK KABUPATEN ACEH TIMUR - Yani Rizal; Safrizal safrizal; Muhammad Fuad (LPPM dan PM Universitas Samudra, 2020)
Pandan handicraft is currently identified as continuing to experience an export market expansion, both domestically and abroad. One of the regions producing pandanus handicraft products in Indonesia is Alue Dua Muka O Village in the Idi Rayeuk District, East Aceh Regency. Based on the results of the situation analysis, it was identified that the pandanus woven craftsmen in the village were still experiencing two main obstacles. The PKM activity was directed towards providing solutions to the two main problems, namely the difficulty of following market demands for the design of pandanus woven crafts, and weaknesses in business management, especially market expansion and use of e-marketing through social media (online shop). After being implemented, this activity gives some relative results and runs smoothly. First, a discussion on developing designs for woven pandanus handicraft products between the Team and the Pandan Craftsmen Group in Alue Dua Muka O Village has also produced a number of ideas that will be realized soon. Second, the business management assistance carried out is considered to be able to motivate group members to be eager to utilize their expertise in weaving pandanas as a source of additional income for their families, as well as being willing to improve group business management for the better future